Development of Guided Discovery-Based E-Module of Momentum Impulse Material to Foster Students’ Digital Literacy - Sumiyati, Sumiyati; Suyidno, Suyidno; Miriam, Sarah; Qamariah, Qamariah (Jurnal Ilmiah Pendidikan Fisika, 2025)
Students' digital literacy remains very lacking. This research aims to determine the feasibility of a guided discovery-based E-Module to train students' digital literacy skills. This research is a research and development study using the ADDIE model, and a practicality test of the E-Module was carried out on 30 physics education alumni in 2017. Data collection techniques employed E-Modul validation instruments and E-Module readability questionnaires. The data analysis technique was quantitative descriptive. The results showed that (1) E-Module validation results and readability instruments in the valid category and (2) E-Module practicality seen from the student readability questionnaire has met the practical category. It is concluded that the E-Module developed on momentum impulse material is feasible to train students' digital literacy skills. This research implies that the integration of digital literacy in modules can help students prepare for the challenges of education in the digital era and encourage the development of a more interactive curriculum.